L'opportunità (e la legittimità) di una nuova vita: Riflessioni sulla conversione nei diritti religiosi a partire da «Sottomissione» di Michel Houellebecq - Pacillo, Vincenzo (Convertirsi, de-convertirsi, riconvertirsi, 2016)
The novel «Submission» can be read as the history of a conversion, the human path of a dissatisfied man who finds again - through a conversion - taste and hope in life and a dimension of equilibrium within the dynamics of existence. Reading the novel, the jurist can reflect on some issues concerning the relationship between the old and the new belonging of the converted faithful, the legitimacy of the proselytism and the validity of a purely formal act of conversion.